2017
DOI: 10.1080/10494820.2017.1372483
|View full text |Cite
|
Sign up to set email alerts
|

Scripting to enhance university students’ critical thinking in flipped learning: implications of the delayed effect on science reading literacy

Abstract: Premised on Web 2.0 technology, the current study investigated the effect of facilitating critical thinking using the Collaborative Questioning, Reading, Answering, and Checking (C-QRAC) collaboration script on university students' science reading literacy in flipped learning conditions. Participants were 85 Taiwanese university students recruited from two introductory educational psychology courses. Groups were formed by affinity grouping and were randomly assigned to collaborative learning conditions with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 38 publications
0
17
0
3
Order By: Relevance
“…Therefore, I suggest that pre-service teachers engage in more Internet-based learning to deal with the challenges derived from the nature and process of Internet-based knowledge claims and knowing. Specifically, instructional and pedagogical strategies featuring information evaluation and computersupported collaborative learning (e.g., Kim & Hannafin, 2016;Lee, 2015Lee, , 2017 may be employed in instruction to facilitate pre-service teachers' critical thinking and to shape their Internet-based epistemic beliefs through individual or collaborative reflection on the uncertainty and structure of Internet-based information and a critical evaluation of knowledge claims by multiple sources.…”
Section: The Impact Of Pre-service Teachers' Epistemic Belief Profilesmentioning
confidence: 99%
“…Therefore, I suggest that pre-service teachers engage in more Internet-based learning to deal with the challenges derived from the nature and process of Internet-based knowledge claims and knowing. Specifically, instructional and pedagogical strategies featuring information evaluation and computersupported collaborative learning (e.g., Kim & Hannafin, 2016;Lee, 2015Lee, , 2017 may be employed in instruction to facilitate pre-service teachers' critical thinking and to shape their Internet-based epistemic beliefs through individual or collaborative reflection on the uncertainty and structure of Internet-based information and a critical evaluation of knowledge claims by multiple sources.…”
Section: The Impact Of Pre-service Teachers' Epistemic Belief Profilesmentioning
confidence: 99%
“…Several approaches (including strategies, models, methods), applied in FC to support the development of CT, included -Collaborative Questioning, Reading, Answering, and Checking‖ (C-QRAC) collaboration script [33], concept mapping-based flipped learning approach [37], RSI (Recognize, Summarize, Inquire)-based flipped approach [8], project-based learning model [38], active learning through discovery and involvement with materials [31], and active learning exercises [34], -… combining collaborative learning with the technique of using Socrates' questioning method and Bloom's taxonomy in designing homework and in-class activities‖ [13]. One study emphasizes pedagogical and technological (mobile technology) supports [27].…”
Section: B Teaching Approaches Used In Flipped Classroom To Develop Ctmentioning
confidence: 99%
“…Besides the advantage in search performance, research demonstrated that students taking matrix notes had lower off-task browsing rate than those not taking note or taking conventional notes (Wu & Xie, 2018). Therefore, it may be helpful to provide students with a structure for note-taking to assist them in prioritizing their attention allocation and gleaning information during online search and reading (e.g., Lee, 2015Lee, , 2018.…”
Section: Online Search and Multitasking: Influence Of Working-memormentioning
confidence: 99%